1981
DOI: 10.1016/s0022-5347(17)54602-9
|View full text |Cite
|
Sign up to set email alerts
|

Major and Minor Complications of Posterior Urethral Valves

Abstract: The true incidence of posterior urethral valves is unknown. They may cause major or minor urinary tract malfunction, reflecting the broad spectrum of degree of congenital malformation. Of 124 boys with posterior urethral valves 76 per cent had only minor secondary abnormalities and 24 per cent had secondary problems, such as large paraureteral diverticula, high grade reflux with upper tract damage, megaureter, hydronephrosis and uremia. The diagnosis of posterior urethral valves was based on voiding cystoureth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 3 publications
2
7
0
1
Order By: Relevance
“…Urodynamic evaluation of 41 patients with PUV by Peters et al (1990) found 3 major categories of bladder dysfunction leading to voiding disturbances: myogenic failure, hyper-reflexia and bladder hypertonia. Kurth et al (1981) confirmed these findings by urodynamic evaluation of 16 boys after valve fulguration.…”
Section: Discussionsupporting
confidence: 63%
“…Urodynamic evaluation of 41 patients with PUV by Peters et al (1990) found 3 major categories of bladder dysfunction leading to voiding disturbances: myogenic failure, hyper-reflexia and bladder hypertonia. Kurth et al (1981) confirmed these findings by urodynamic evaluation of 16 boys after valve fulguration.…”
Section: Discussionsupporting
confidence: 63%
“…It is observed that there is no much difference regarding the renal status in our study from other studies. 17,[20][21][22] In our study obstructive features are detected in 33 (73.33%) cases by USG, in 39 (86.67%) cases by VCUG and are confirmed in 33 (73.33%) cases at the time of cystoscopy. Various authors used voiding cystourography as the main diagnostic tool assisted by Intravenous Urography (IVU) and ultrasonography of KUB region to study the renal status.…”
Section: Discussionsupporting
confidence: 52%
“…A weak urinary stream has been reported in less than 30 percent of cases, so that a strong stream does not preclude the diagnosis of posterior urethral obstruction. 16,17 The gold standard for diagnosis remains the radiographic voiding cystourethrography and retrograde urethrography. 18,19 Prenatal ultrasound screening of PUV has significantly increased early diagnosis and management of this pathology in most developed societies.…”
mentioning
confidence: 99%
“…In severe cases of PUV, two important factors, reflux [ 12] and high‐pressure detrusor storage [ 19], decrease the efficiency of ureteric urinary transport. VUR has been reported in 19–72% of children with PUV and an even higher percentage in those with more severe PUV [ 20].…”
Section: Primary and Secondary Pathologymentioning
confidence: 99%